PENERAPAN METODE WATERFALL DALAM PEMBANGUNAN SISTEM INFORMASI KEHADIRAN DAN HONORARIUM GURU SMK CITRA MUTIARA BEKASI - Agustiana, Irma; Syamsiah, Nurfia Oktaviani (www.bsi.ac.id, 2016)
This study provides problem solution with the use of computer-based data processing technology to overcome the problems in the system and calculating attendance honorarium of teachers, especially in SMK Citra Mutiara. Where errors occur often recapitulation presence that cause financial losses for teachers and school management. Each of the existing step from analysis to implementation using the Waterfall method. This study tested using blackbox testing. This system is implemented using Micrososft Visual Basic 6.0 and Microsoft Acess 2003 as DBMS. Attendance system and payment of honorarium teachers gives more accurate presence information and the calculation of the honorarium of teachers becomes more effective.Keywords: presence, honorarium teacher, waterfall.